Deciphering the binding mechanism of an anti-cancer phytochemical plumbagin with calf thymus DNA using biophysical and in silico techniques - Rahaman, Abdul; Anjum, Farah; Kumari, Aknita; Shafie, Alaa; Alee, Mahafooj; Badr, Omnia; Khan, Shaheer Hasan; Ashour, Amal Adnan; Hazazi, Ali; Arif, Sultan; Zeng, Xin-An (Frontiers in Chemistry, 2023)
Plumbagin (PLM), a plant derivative, is well known for a wide range of therapeutic effects in humans including anti-cancer, anti-inflammatory, anti-oxidant, and anti-microbial.Cytotoxic and genotoxic potential of this phytochemical has been studied which demands further insight. DNA being a major target for several drugs was taken to study against PLM to understand its effects on the cellular system. UV-Vis spectroscopy has indicated the binding of PLM to ctDNA and dye displacement assays have confirmed the formation of PLM-ctDNA complex. The insignificant changes in circular dichroism spectra suggested that PLM is not affecting the structural makeup of the ctDNA, hence the binding could be peripheral and not intercalating. Further, the relative viscosity and minimal change in melting temperature upon the complex formation supported this finding and confirmed the groove binding of PLM. Molecular docking analysis and simulation studies also show PLM as a minor groove binder to DNA and provide details on the interaction dynamics of PLM-DNA complex. Docking followed by a 100 ns simulation reveals the negative Gibbs free energy change (∆G = -6.6 kcal mol -1 ), and the formation of a stable complex. The PLM-DNA complex with stable dynamics was further supported by different parameters including RMSD, RMSF, SASA, Rg, and the energy profile of interaction. This study provides an insight into the cytotoxic and genotoxic mechanism of PLM which can be a crucial step forward to exploit its therapeutic potential against several diseases including cancer.